Bila ABRI berbisnis : buku pertama yang menyingkap data dan kasus penyimpangan dalam praktik bisnis kalangan militer - Samego, Indria, 1950- (Bandung : Mizan, 1998)
Business practices of the Indonesian Armed Forces as well as of military individuals
Includes bibliographical referencses (p. 199-203) and index
Keywords: Indonesia. -- Angkatan Bersenjata; Military-owned business enterprises -- Indonesia